A Jumputan or Songket Waste Used As A Preventive Mask For Covid 19 In South Sumatra Indonesia - Masnunah Masnunah (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This research has a purpose namely utilization of jumputan cloth or songket into a mask to help the Regional Government program in preventing Covid-19 Virus in South Sumatra. Design/methodology/approach: Research methods form of descriptive method, analysis of the data used in the form of documentation and questionnaires. Findings: The results showed that the importance of adhering to health protocols, especially using masks, was seen from student responses, namely 96.43 % in the Very High category. Research output in the form of products in the form of masks from waste cloth jumputan or songket cloth. Research limitations/implications: There has been no clinical test for this study to determine the effectiveness of Jumputan or Songket. Practical implications: The result of this research can be used as a reference in overcome Covid-19 cases. Originality/value: Jumputan or songket can be an alternative solution in the series of handling the Covid 19 cases. Paper type: Research Paper